Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Mediasi pada PT. Makmur Orient Jaya - Pangestu, Mikko Media; Setyaningrum, Retno Purwani (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of work motivation and work environment on employee performance with job satisfaction as a mediating variable at PT Makmur Orient Jaya. The study used a quantitative approach with a causal design. Data were collected through a Likert scale questionnaire 1–5 to 100 employees selected using a purposive sampling technique. Data analysis was performed using Partial Least Square Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4.0. The results showed that work motivation and work environment have a positive and significant effect on employee performance and job satisfaction. Job satisfaction also has a positive and significant effect on employee performance. In addition, job satisfaction is proven to partially mediate the influence of work motivation and work environment on employee performance. The R² value of 0.538 indicates that work motivation, work environment, and job satisfaction are able to explain 53.8% of the variation in employee performance. This finding confirms that improving employee performance depends not only on strengthening motivation and creating a conducive work environment, but also on increasing job satisfaction as an important mechanism that strengthens the influence of both factors on employee performance.